LTE Advanced Network Performance Analysis for Smartfren and Telkomsel in the City of Yogyakarta - Widyasmoro Widyasmoro (Universitas Muhammadiyah Yogyakarta, 2023)
This study investigates comprehensive assessment of LTE-Advanced network performance in urban environment of Sudirman Road and Malioboro Road, Yogyakarta, Indonesia. This study aims to measure and assess the performance or quality of the LTE-Advanced network based on the Quality of Service (QoS) and Signal Strength parameters using the drive test measurements data collection method. This study analyses signal strength parameters (RSRP and RSRQ) and quality of service metrics (delay and jitter) across two prominent operators, Smartfren and Telkomsel. Our investigation unveils robust signal strength from both operators at Sudirman Road, with Smartfren demonstrating notable superiority in RSRQ. Similarly, at the Malioboro Road, both operators exhibit commendable RSRP, with Smartfren maintaining a marginal advantage. In terms of quality of service, our findings affirm that both Smartfren and Telkomsel consistently deliver low latency and maintain satisfactory jitter levels, ensuring uninterrupted connectivity experiences for users. While Telkomsel typically leads in delay performance, Smartfren showcases superior jitter performance at specific points at Sudirman Road. Conversely, at Malioboro Road, Telkomsel outperforms Smartfren in both delay and jitter metrics. These insights offer invaluable guidance for network optimization strategies, empowering operators to enhance service quality and enrich connectivity for the users in Yogyakarta. Furthermore, our study contributes to the broader understanding of LTE-Advanced network performance, emphasizing the significance of signal strength and quality of service parameters in ensuring optimal user experiences in urban environments.